Investigation into the restoration of TRPM3 ion channel activity in post-COVID-19 condition: a potential pharmacotherapeutic target - Sasso, Etianne Martini; Muraki, Katsuhiko; Eaton-Fitch, Natalie; Smith, Peter; Jeremijenko, Andrew; Griffin, Paul; Marshall-Gradisnik, Sonya (Frontiers in Immunology, 2024)
Recently, we reported that post COVID-19 condition patients also have Transient Receptor Potential Melastatin 3 (TRPM3) ion channel dysfunction, a potential biomarker reported in natural killer (NK) cells from Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) patients. As there is no universal treatment for post COVID-19 condition, knowledge of ME/CFS may provide advances to investigate therapeutic targets. Naltrexone hydrochloride (NTX) has been demonstrated to be beneficial as a pharmacological intervention for ME/CFS patients and experimental investigations have shown NTX restored TRPM3 function in NK cells. This research aimed to: i) validate impaired TRPM3 ion channel function in post COVID-19 condition patients compared with ME/CFS; and ii) investigate NTX effects on TRPM3 ion channel activity in post COVID-19 condition patients. Whole-cell patch-clamp was performed to characterize TRPM3 ion channel activity in freshly isolated NK cells of post COVID-19 condition (N = 9; 40.56 ± 11.26 years), ME/CFS (N = 9; 39.33 ± 9.80 years) and healthy controls (HC) (N = 9; 45.22 ± 9.67 years). NTX effects were assessed on post COVID-19 condition (N = 9; 40.56 ± 11.26 years) and HC (N = 7; 45.43 ± 10.50 years) where NK cells were incubated for 24 hours in two protocols: treated with 200 µM NTX, or non-treated; TRPM3 channel function was assessed with patch-clamp protocol. This investigation confirmed impaired TRPM3 ion channel function in NK cells from post COVID-19 condition and ME/CFS patients. Importantly, PregS-induced TRPM3 currents were significantly restored in NTX-treated NK cells from post COVID-19 condition compared with HC. Furthermore, the sensitivity of NK cells to ononetin was not significantly different between post COVID-19 condition and HC after treatment with NTX. Our findings provide further evidence identifying similarities of TRPM3 ion channel dysfunction between ME/CFS and post COVID-19 condition patients. This study also reports, for the first time, TRPM3 ion channel activity was restored in NK cells isolated from post COVID-19 condition patients after in vitro treatment with NTX. The TRPM3 restoration consequently may re-establish TRPM3-dependent calcium (Ca 2+ ) influx. This investigation proposes NTX as a potential therapeutic intervention and TRPM3 as a treatment biomarker for post COVID-19 condition.